Critical factors of electricity consumption in residential buildings: An analysis from the point of occupant characteristics view. (20th May 2020) - Xu, Xiaoxiao; Xiao, Bing; Li, Clyde Zhengdao
Abstract: Occupant characteristics are critical factors that have a significant impact on electricity consumption in residential buildings, which have attracted increasing attention in the research field of building energy. This study analyses the influencing of occupant characteristic-related factors on electricity consumption in residential buildings with the consideration of different targets of electricity consumption, particularly by developing a statistical model based on a large data set published by the US Department of Energy. Results show that ECRB can be substantially affected by occupant characteristic-related factors, including 'age of householders', 'household size', 'income', 'education level', 'type of occupancy' and 'length of residency'. They could explain 10.70% of the variance in electricity consumption. In which, type of occupancy' has the largest impact, followed by 'education level', 'length of residency', 'household size' and 'income'. It is also found that there are differences between some occupant characteristics corresponding to different occupant behaviors. Additionally, this study conducted an in-depth analysis of the relationship between occupant behaviour (including the use of energy star appliances, frequency appliances used, energy audit and insulation adding) and occupant characteristic-related factors. The analysis method serves as an effective tool for quantitatively evaluating the effect of various occupant characteristics in occupant behaviour modelling and building energy simulation, offering valuable references for practitioners, such that the appropriate strategies for electricity consumption saving can be selected in advanced. Highlights: Critical factors influencing electricity consumption in the point of occupant characteristic view. Analyse the influencing mechanism of occupant characteristics on electricity consumption. An effective tool for quantitatively evaluating the effect of various occupant characteristics.